Vitamin D level in Rheumatoid arthritis and its correlation with the disease activity - Soha Sayed Shaaban; Amany Fayez Hakim (Journal of Medicine in Scientific Research, 2019)
Objective Vitamin D has an immunomodulatory and anti-inflammatory action, and its deficiency may cause several autoimmune disorders, including rheumatoid arthritis (RA). The relationship between vitamin D level and the severity of RA is of mere interest to several researchers. Patients and methods This prospective study included 40 cases of RA and 20 healthy controls, of age group between 40–70 years. Serum Vitamin D levels were measured and compared in RA patients and controls. Vitamin D levels in RA patients were measured in three different groups; active RA group, inactive RA group and control. Results Sixty-five percent patients of active RA were Vitamin D deficient versus only 40% of inactive RA patients. The serum Vitamin D levels were also significantly lower in the RA patients (mean value of 18.09 ± 8.99 ng/ml), as compared to the controls (mean value of 29.67 ± 11.34 ng/ml). There was an inverse significant correlation between serum Vitamin D levels and RA disease activity as measured by DAS28. The mean serum Vitamin D levels were 18.81 ± 6.679 ng/ml, 14.42 ± 6.856 ng/ml, 9.83 ± 6.791 ng/ml, in low disease activity, moderate disease activity, and high disease activity groups, respectively. Conclusion Vitamin D deficiency is more common in autoimmune diseases as RA and may be one of the leading cause of increased disease activity.